ESTIMATION OF VARIANCE COMPONENTS AND HERITABILITY FOR STAYABILITY IN HOLSTEIN AND BROWN SWISS CATTLE - Ledesma Rodríguez, Anel; Calderón Robles, René Carlos; Ríos Utrera, Ángel; Martínez Velázquez, Guillermo; Montaño Bermúdez, Moisés; Flores Primo, Argel; Canseco Sedano, Rodolfo; Vicente Martínez, Jorge Genaro; Vega Murillo , Vicente Eliezer; Baeza Rodríguez, Juan José (Chilean Journal of Agricultural & Animal Sciences, 2024)
Stayability (STAY) reflects the ability of a cow to avoid both voluntary and involuntary culling. The present study aimed to estimate variance components and heritability for STAY in Holstein and Brown Swiss cattle. Genealogical and productive data from 340 cows were used. The data were provided by Las Margaritas experimental farm, belonging to the National Institute of Forestry, Agricultural and Livestock Research of Mexico. STAY was defined as a cow's probability of achieving a specific lactation. STAY traits analyzed were the probabilities that a cow had one (STAY1), two (STAY2), three (STAY3), four (STAY4), and five (STAY5) lactations, given that it had a first calving. Variance components and heritability were estimated with the ASREML statistical software. An animal threshold model was fitted. It included the fixed effect of the contemporary group and the covariate percentage of Holstein genes, heterozygosity, and recombination loss. The direct additive genetic effect was included as a random effect. Heritability values of 0.33 ± 0.33, 0.23 ± 0.11, 0.27 ± 0.09, 0.24 ± 0.09 and 0.29 ± 0.09 were obtained for STAY1, STAY2, STAY3, STAY4 and STAY5, respectively. The heritability values ??obtained were in the range of low to moderate, which suggests that the traits could be taken into account in future genetic selection programs.